Crafting A Stronger Workforce: An Exploration of Mindset, Personality, and Stress For A Work Resiliency Framework at Bataan Peninsula State University - Rosemarie Farro (Jurnal Ilmu Pendidikan dan Budaya, 2026)
High performance standards in the dynamic academic environment often trigger stress and burnout, threatening even the most resilient educators. This study examines the determinants of work resiliency among 149 faculty members at Bataan Peninsula State University (BPSU) to design a robust institutional framework. Utilizing a descriptive-correlational design with Partial Least Squares-Structural Equation Modeling (PLS-SEM), the research evaluates the interplay between mindset, personality traits, and stress levels. Findings demonstrate that mindset ( β = 0.313, p < .001), personality (β = 0.111, p = .013), and stress (β = -0.26, p = .002) significantly predict resiliency. Notably, stress serves as a crucial mediator in the relationship between mindset and work resiliency (β = 0.327, p < .001), suggesting that a growth-oriented mindset mitigates the negative impact of workplace pressures. Based on these empirical results, a Work Resiliency Framework is proposed, integrating strategic interventions to cultivate growth mindsets, reinforce positive personality traits, and implement systematic stress management. This framework serves as a strategic blueprint for academic institutions to sustain faculty well-being and professional excellence amidst evolving educational demands.